The Relationship Between Mother’s Knowledge About Exclusive Breastfeeding and Husbands' Support for Breastfeeding Mothers with Exclusive Breastfeeding at the Sedap Malam Posyandu in South Tangerang City - Sinabutar, Nerli Adria; Lestari, Puji; Saraswati, Dewa Ayu (PROMOTOR, 2024)
Background: Breast milk (ASI) is food and drink without other additions to infants aged 0-6 months, Exclusive means that babies from birth to 6 months of age are only given breast milk without any other additional fluids. Research Objective: This study aims to determine the relationship between maternal knowledge and husband's support for exclusive breastfeeding at Posyandu Sedap Malam on the success of breastfeeding. Research Methodology: This study was a quantitative design with a cross-sectional approach. This study used the Fishe Exact Test. The population and samples in this study were breastfeeding mothers in Sedap Malam Posyandu, Pamulang Barat Village as many as 40 people. Research Results: m Maternal Knowledge of Exclusive Breastfeeding obtained the results of Good Knowledge of Non-Exclusive 1 (20%) respondents and Exclusive Breastfeeding 4 (80%) respondents, Fair Knowledge of Non-Exclusive 3 (15%) respondents and Exclusive Breastfeeding 17 (85%) respondents, Poor Knowledge of Non-Exclusive 3 (20%) respondents and Exclusive Breastfeeding 12 (80%) respondents with the results Pvalue 0.173). Conclusion: The results of this study with the Fisher Exact Test found that the results of statistical tests with p value (0.173) > 0.05 with the hypothesis Ho is accepted, which means that there is no relationship between maternal knowledge of exclusive breastfeeding and the results of statistical tests obtained pvalue (0.154) > 0.05 and the hypothesis Ho is accepted, which means that there is no relationship between husband's support for exclusive breastfeeding at Posyandu Sedap Malam, South Tangerang City in 2024. Suggestion: Based on the results of this study, it is hoped that health services should provide information in increasing exclusive breastfeeding to breastfeeding mothers at the Sedap Malam Posyandu.